2013
DOI: 10.1002/14651858.cd006313.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous versus inhalation anaesthesia for one-lung ventilation

Abstract: Very little evidence from randomized controlled trials suggests differences in participant outcomes with anaesthesia maintained by intravenous versus inhalational anaesthesia during one-lung ventilation. If researchers believe that the type of drug used to maintain anaesthesia during one-lung ventilation is important, they should design randomized controlled trials with appropriate participant outcomes, rather than report temporary fluctuations in physiological variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 51 publications
0
23
0
3
Order By: Relevance
“…This may reflect the theoretical benefits of TIVA to the thoracic anaesthetist in terms of preservation of hypoxic pulmonary vasoconstriction, as well as the convenience of separating the provision of anaesthesia from airway maintenance and lung isolation . Although a 2013 Cochrane review concluded “ that no evidence indicated that the drug used to maintain anaesthesia during one‐lung ventilation affected participant outcomes ” there is a significant body of randomised controlled trial data suggesting a reduced incidence of pulmonary inflammation and/or pulmonary complications in thoracic patients receiving volatile anaesthesia . This is perceived to stem from an immunomodulatory effect of volatile anaesthesia .…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect the theoretical benefits of TIVA to the thoracic anaesthetist in terms of preservation of hypoxic pulmonary vasoconstriction, as well as the convenience of separating the provision of anaesthesia from airway maintenance and lung isolation . Although a 2013 Cochrane review concluded “ that no evidence indicated that the drug used to maintain anaesthesia during one‐lung ventilation affected participant outcomes ” there is a significant body of randomised controlled trial data suggesting a reduced incidence of pulmonary inflammation and/or pulmonary complications in thoracic patients receiving volatile anaesthesia . This is perceived to stem from an immunomodulatory effect of volatile anaesthesia .…”
Section: Discussionmentioning
confidence: 99%
“…13 Alternatively, a recent review found little evidence for differences in outcomes between inhalation and intravenous anesthesia during lung surgery. 14 The purpose of this study was to compare the effect of sevoflurane vs propofol anesthesia on postoperative neurocognitive test scores and cerebral oxygenation parameters in a population of patients undergoing lung surgery. The primary outcome was defined as the incidence of POCD on postoperative day five.…”
Section: Résumémentioning
confidence: 99%
“…In contrast to total intravenous anesthesia, the use of sevoflurane or desflurane inhalation anesthesic can inhibit the release of inflammatory mediators in local cells, reduce the role of inflammatory factors, thereby reducing the inflammation of the ventilation lung. Modolo [8] and others summed up 20 comparative studies about anesthesia and inhalation anesthesia for single lung ventilation,then achieved a meta-analysis that pointed out there is no strong evidence making sure that anesthetic drugs will affect the prognosis of patients. Dupont [9] also reported that the impact of sevoflurane and desflurane on hemodynamics in patients with pulmonary surgery had no statistically significant difference, but desflurane group woke up faster and earlier.…”
Section: Discussionmentioning
confidence: 99%